Uveitis-related Factors in Patients With Spondyloarthritis: TReasure Real-Life Results - ATAGÜNDÜZ, MEHMET PAMİR (ELSEVIER SCIENCE INC, 2021)
PURPOSE: Spondyloarthritis (SpA) is a group of diseases with overlapping skeletal and extra-articular features. Acute anterior uveitis (AAU) is the most common extra-articular manifestation of SpA. The relation between AAU and SpA is well defined in the current literature. Our study aims to analyze the frequency and factors associated with AAU in different forms of SpA in a large nationwide cohort of Turkish SpA patients. DESIGN: Retrospective cohort study. METHODS: The data were obtained from the TReasure database, which compiles data from records of the web-based Rheumatoid Arthritis (RA) and SpA patients treated with biological disease-modifying anti-rheumatismal drugs from different regions of Turkey. The clinical characteristics of SpA and uveitis are recorded. RESULTS: Data of the 4,297 SpA patients were included in the study. Overall, 475 of 4,297 patients (11.0%) had experienced 1 or more episodes of uveitis. SpA patients with older age (P<.001), a smoking history (P=.004), delayed diagnosis (P=.001), longer disease duration (P<.001), arthritis (P<.001), positive HLA-B27 (P<.001), a family history of SpA (P<.001), and radiographic damage (presence of sacroiliitis, syndesmophytes, bamboo spine, hip involvement) (P<.001 for all) more commonly had uveitis. On the other hand, uveitis was less prevalent in patients with psoriasis and psoriatic arthritis (P<.001 for both). CONCLUSION: Uveitis may be the key feature leading to SpA diagnosis. Patients with radiographic damage and long disease duration have an increased risk for uveitis in both male and female SpA patients. Patients with uveitis should be referred to a rheumatologist for a thorough evaluation of SpA. ((C) 2021 Elsevier Inc. All rights reserved.)
Keywords: ANKYLOSING-SPONDYLITIS; ANTERIOR UVEITIS